Konsentrasi antioksidan melatonin saliva pada pasien periodontitis kronis - Gani Soulisa, Abdul; Andayani, Lia Hapsari (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background : Melatonin is a natural antioxidant produced by human body which has various functions for human health. Melatonin has an anti-inflammatory effect as an antioxidant, neutralizes free radicals, and supports collagen and bone formation. Aim : This study aimed to assess the concentration of salivary antioxidant melatonin in patients with chronic periodontitis. Methods : A total of 18 participants under 45 years old were selected using purposive sampling at RSGM-P FKG Usakti. Saliva samples (1 ml) were collected in the morning. The Mann-Whitney test was applied to compare melatonin levels between healthy individuals and those with chronic periodontitis. Results : Mean of salivary melatonin concentration was lower in chronic periodontitis patients (77.72 ± 81.78) compared to healthy individuals (85.28 ± 54.50), though this difference was not statistically significant (p = 0.479). Conclusion : Despite lower salivary melatonin levels in patients with chronic periodontitis, the difference was not statistically significant.